2021
DOI: 10.1093/fampra/cmab042
|View full text |Cite
|
Sign up to set email alerts
|

‘I was scared I will end up in another abortion’: a mixed-methods study assessing the impact of COVID-19 pandemic and lockdown on the antenatal care of pregnant women in Puducherry, South India

Abstract: Background As a mitigation measure for COVID-19 pandemic, lockdown was implemented in India for a period of 2 months (24 March–31 May 2020). Disruption in antenatal care (ANC) provisions during lockdown is expected due to diversion of public health facilities on pandemic. Objective To assess the proportion of pregnant women who had not completed the ideal number of antenatal visits, availability of iron–folic acid (IFA) suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 18 publications
0
18
0
1
Order By: Relevance
“…Out of 150 pregnant women, 41% of women did not complete the ideal number of visits and 40% developed health problems. Major challenges to health service access included economic hardships, restricted mobility, lack of information about health system changes, and psychological stress [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Out of 150 pregnant women, 41% of women did not complete the ideal number of visits and 40% developed health problems. Major challenges to health service access included economic hardships, restricted mobility, lack of information about health system changes, and psychological stress [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Information on obstetric characteristics and details regarding antenatal and to understand the perceived challenges in availing of health services were collected through telephonic interviews during the lockdown period. (14) In 2018, Ahamad F et al conducted a community-based open-labeled parallel block randomized controlled trial among 400 pregnant women in a rural area of Haryana north India. In the intervention group, the first time IFA supplementation was given by ASHA workers every week and after being given the first dose pregnant women were counseled to take the remaining tablets during the week as per the advice by a health professional.…”
Section: Resultsmentioning
confidence: 99%
“…Women who were counseled by health care professionals about IFA supplementation, its correct dosage, time of administration, benefits, and its importance were more likely to be associated with good compliance. (18,14,(19)(20)(21) Six studies also showed the association of history of anemia and knowledge about anemia with the compliance of IFA supplementation. Most of the studies showed that pregnant women who knew about anemia were significantly associated with good compliance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have identified the shortfalls in the provision and utilization of routine MCH services during the current pandemic. A drop in utilization of antenatal care (ANC) and post-natal care (PNC) [ 5 , 6 ], institutional delivery [ 7 ], routine immunization services [ 8 , 9 ], and family planning services [ 10 ] signifies the lapses in MCH care due to the COVID-19 pandemic. Prior to the onset of the pandemic, the state of Odisha was making great efforts to improve its maternal and child health indicators [ 11 ] to achieve the figures targeted under sustainable development goals (SDG).…”
Section: Introductionmentioning
confidence: 99%